2018
DOI: 10.18311/jbt/2018/21170
|View full text |Cite
|
Sign up to set email alerts
|

Has Demonetisation Pushed Digitalisation in India? Some Counter Evidences

Abstract: India witnessed demonetisation in November 2016, when high value denomination notes of Rs. 500 and Rs. 1000 were withdrawn at a single stroke which extinguished about 86 percent of the total currency value in circulation. Demonetisation which aimed to curb black money, terror funding and counterfeiting at the first place, was later projected as the government's push for digitalisation drive. In this paper, we analyse the effect of demonetisation on digital payments viz. debit card, point of sale transactions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Tilakaratna posits that, the adoption of technology is dependent on the personal beliefs of the user as well as the immediate external environment in which they operate. Research have shown that, people believe technology use to be advantageous, reducing mental and physical effort [33,34]. These prior studies showed that consumer trust is as important in adopting financial products and services of banks as the widely accepted TAM use-antecedents, perceived ease of use and perceived usefulness.…”
Section: Technology Acceptance Model (Tam) Theorymentioning
confidence: 99%
“…Tilakaratna posits that, the adoption of technology is dependent on the personal beliefs of the user as well as the immediate external environment in which they operate. Research have shown that, people believe technology use to be advantageous, reducing mental and physical effort [33,34]. These prior studies showed that consumer trust is as important in adopting financial products and services of banks as the widely accepted TAM use-antecedents, perceived ease of use and perceived usefulness.…”
Section: Technology Acceptance Model (Tam) Theorymentioning
confidence: 99%
“…Gefen, Karahanna and Straub (2003) studied a separate and distinct interaction of both the actual e-vendor and with its IT Web site interface is at the heart of online shopping. Previous research has established, accordingly, that online purchase intentions are the product of both consumer assessments of the IT itselfspecifically its perceived usefulness and ease-of-use (TAM)-and trust in the e-vendor (Nithin & Baiju, 2018). The research showed that consumer trust is as important to online commerce as the widely accepted TAM use-antecedents, perceived usefulness and perceived ease of use.…”
Section: Literature Diffusion Of Innovation Theory (Doi)mentioning
confidence: 99%
“…Gefen, Karahanna and Straub (2003) studied a separate and distinct interaction of both the actual e-vendor and with its IT Web site interface is at the heart of online shopping. Previous research has established, accordingly, that online purchase intentions are the product of both consumer assessments of the IT itself-specifically its perceived usefulness and ease-of-use (TAM)-and trust in the e-vendor (Nithin & Baiju, 2018). The research showed that consumer trust is as important to online commerce as the widely accepted TAM use-antecedents, perceived usefulness and perceived ease of use.…”
Section: Theoretical Foundationmentioning
confidence: 99%